UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA MATA PELAJARAN MATEMATIKA SISWA KELAS IIID DI SDN RAWAMANGUN 01 PAGI - Novianti, Amelia; Iva Sarifah; Julius Sagita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT Mathematics is one of the subjects studied at the elementary school level from lower to upper grades. In learning mathematics, critical thinking skills are needed in solving the given problems. For this reason, critical thinking skills are very necessary for learning mathematics. However, students' critical thinking skills in mathematics, especially in class IID, have not shown good results. The purpose of the research in this article is to improve the critical thinking skills of class IIID students in mathematics, the material for presenting data in tabular form at SDN Rawamangun 01 Pagi. This study uses the Kemmis and Taggart research model which consists of 4 stages, namely planning, implementation and observation and reflection. Researchers carry out learning actions with the cooperative learning model of the think pair share type. Data analysis that has been carried out shows an increase in students' critical thinking skills, after the implementation of the first cycle, the presentation of results was obtained at 46.16%, namely only eleven students who got a score above 70, meaning that students' critical thinking skills have not reached the specified target of 80%. Meanwhile, in the data from cycle 11, there was an increase to 82.60, namely there were 19 students who got a score above 70. This means that there was an increase of 36.44% which shows that the application of the think pair share type cooperative learning model can be said to be successful in improving students' critical thinking skills regarding data presentation material in tabular form. Keywords: Critical Thinking, Think Pair Share Learning Model, Elementary School